A Comparative Study on Impact of Structured Physical Activity on Self-Esteem and Self-Concept in Children (International Journal of Food and Nutritional Sciences, 2025)
Physical activity offers not only the body with physical health but also has a tremendous effect on psychological well-being especially for the child. Self-esteem and self-concept influence the confidence of children, their emotional stability and interaction among them. This study looks into how structured physical activity impacts these psychological dimensions among children aged between 8 and 12 in Gwalior India. In the 12-week intervention a total of 100 children were involved: 50 with structured physical activity sessions and 50 in control groups maintaining their usual routines. Before and after the intervention self-esteem and self-concept were assessed by Rosenberg Self-Esteem Scale (RSES) and Piers-Harri ' Children's Self-Concept Scale. It was found that there were highly significant improvements in the experimental group but not much changes occurred in control groups. This study pointed out the need for scheduled physical activity at school and community level to help children in urban India develop positive mental well-being.